Improved sulfur nutrition provides the basis for enhanced production of sulfur-containing defense compounds in Arabidopsis thaliana upon inoculation with Alternaria brassicicola - Kruse, Cordula; Haas, Florian Heinrich; Wirtz, Markus; Hell, Rüdiger (Journal of plant physiology, 2012)
The antifungal activities of many sulfur-containing defense compounds suggest a connection between pathogen infection, primary sulfur metabolism and sulfate nutritional status of plants. This relationship was investigated using Arabidopsis thaliana plants that were cultivated under different sulfur regimes and challenged by Alternaria brassicicola. Plants grown with 500 μM sulfate were significantly less infected compared to plants grown on 50 μM sulfate. Upon infection, the formation of the sulfur-containing defense compound camalexin and the gene expression of the sulfur-rich defense peptide defensin were clearly enhanced in plants grown with an optimal compared to a sufficient sulfate supply in the growth medium. Elevated levels of sulfite and O-acetylserine and cysteine biosynthetic enzymes after infection indicated a stimulation of sulfur metabolism under the higher sulfate supply. The results suggest that, in addition to pathogen-triggered activation of sulfur metabolism and sulfur-containing defense compound formation, the sulfate nutritional status is sensed to contribute to plant defense.
Gesehen am 16.05.2017